4ab-3a+3bx-2ab anyone know the answer to this problem?

Answers

Answer 1
Answer:

Answer:

-3a+3bx+2ab

Step-by-step explanation:


Related Questions

What is 5 88/100 - 1 94/100
help!!!! It’s missing and I forgot to do but I need the answers 1-4 thank you so much your a life saver
If you get this you are a critical thinker.I enter the garden.There are 34 people.You kill 30.How many people are in the garden.Good luck!If you get it correct your answer will be deleted and l will message you to continue the game.Don't play if you are not going to continue party poopers! I won against Lisa Swensrud​
Which equation could have been used to create this function table? A.y = 4xB.y = 5xC.y = x + 7D.y = x + 2
QuestionCalculate the arc length for a circle whose radius is 6 with a central angle θ=135°. S=

Which algebraic expression has a term with a coefficient of 9? O A. 6(x + 5) O B. 6x - 9 O C. 6+ x - 9 O D. 9x=6​

Answers

Answer:

D is the answer to your question

Find the slope using the formula.
(4, 19) and (2, 11)

Answers

Answer:

m=4

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS

Algebra I

  • Slope Formula: m=(y_2-y_1)/(x_2-x_1)

Step-by-step explanation:

Step 1: Define

(4, 19)

(2, 11)

Step 2: Find slope m

  1. Substitute:                    m=(11-19)/(2-4)
  2. Subtract:                       m=(-8)/(-2)
  3. Divide:                          m=4

Evaluate each function.k(a) = |-2a + 3| - 1; Find k(3).

g(x) = 4^2x-1 + 7; Find g(1).

f(x) = |8x^2 - 5x + 3|; Find f(-2).

h(x) = -3x + 9; Find h(-1 + x).

f(n) = 5n - 1, Find f(- 3n).

Answers

Step-by-step explanation:

k(a) = | -2a + 3 | - 1

k(3) = | -2(3) + 3 | - 1        replaced the a with 3

      = | -6 + 3 | - 1

      = | -3 | - 1

      =    3   - 1

      = 2

g(x) = 4²ˣ⁻¹ + 7

g(1) = 4²⁽¹⁾⁻¹ + 7                 replaced the x with 1

      = 4¹ + 7

      = 4 + 7

      = 11

f(x) = | 8x² - 5x + 3 |

f(-2) = | 8(-2)² - 5(-2) + 3 |        replaced the x with -2

      = | 8(4) - 10 + 3 |

      = | 12 - 10 + 3 |

      = | 5 |

      = 5

h(x) = -3x + 9

h(-1 + x) = -3(-1 + x) + 9          replaced the x with -1 + x

            = 3 - 3x + 9

            = 12 - 3x

f(n) = 5n - 1

f(-3n) = 5(-3n) - 1                 replaced the n with -3n

        = -15n - 1

What is the equation of the line through the origin and (-5, 6)?O A. y = -5x
O B. y = -6/5 x
O C. y = -6x
0 D. y = -5/6 x

Answers

Answer:

answer is option b

Step-by-step explanation:

B. y=-6/5x

Factor out the GCF of (2x+1)

Answers